PENGARUH MODEL PEMBELAJARAN INKUIRI TERBIMBING BERBANTUAN PhET SIMULATIONS TERHADAP KETERAMPILAN PROSES SAINS SISWA PADA MATERI PEMANTULAN DAN PEMBIASAN CAHAYA - Djola, Tita Aprianti; Abdjul, Tirtawaty; Ntobuo, Nova Elysia (JPFT (Jurnal Pendidikan Fisika Tadulako Online), 2021)
This study aimed to see the effect of using learning models guided inquiry assisted by PhET simulations of students' science process skills at material on reflection and light refraction at SMP Negeri 4 Telaga. The research method used is experimental research with a quantitative approach and use study design One Group Pretest-posttest design. Data collection techniques through tests essay. The collected data were processed and analyzed using the t test statistic, where the test results The hypothesis will be based on the minimum completeness criteria, namely 70. From the results of hypothesis testing obtained t arithmetic amounted to 5.08 and the t table for 1.71, so the value of t arithmetic greater than t table can It is concluded that H i is rejected, in this case H 0 is accepted. Based on the normalized gain results Also obtained a result of 0.721 this means it is in the high category. This matter shows that the use of guided inquiry learning model assisted by PhET Simulations have a positive effect on students' science process skills.